An Occasion for Celebration; but Global Worries Lie Ahead. Issue 4 (24th October 2018) - Crouch, Colin
Abstract: Ideas developed by the social democratic left have been brought together in Prosperity and Justice . Contributors from a wide spectrum of backgrounds have contributed to a new post neoliberal consensus. More attention needs to be paid to the global level of policy making. International capacity to act is declining just as the need for it grows. Political movements seeking to reassert nationalism against global collaboration are growing. Economic policies cannot be replaced without considering the global institutional structure.